Basic Needs Adversities Among Counselors in Training: A Cluster Analysis - Jamie E. Crockett; Nathaniel N Ivers (Teaching and Supervision in Counseling, 2023)
During the intersection of COVID-19 with ongoing identity-based injustices in the US, Counselors-in-Training (CITs) experience unprecedented challenges including new or exacerbated basic needs insecurity. In this descriptive study, the authors examined Basic Needs Adversities (BNA) in a national sample of CITs (n = 233) during the first year of the COVID-19 pandemic. The authors used cluster analysis to investigate CITs reported BNAs and identified four subgroups of participants based on similarities and dissimilarities in the number and type of BNAs endorsed. The authors discuss implications for training and supervision with a focus on social justice in counselor education.
Keywords: Basic Needs Adversities; Identity-based injustice; Social justice; Counselors in training; COVID-19